Comparison of Two Different Earthquake Sources for the 26 December 2004 Aceh Tsunami Simulation - Puspito, Nanang T.; Gunawan, Indra (ITB Journal Publisher, LPPM ITB, 2006)
The tsunami wave propagation of the 26 December 2004 Aceh tsunami has been studied by performing a numerical tsunami simulation based on a method that was originally developed by the Tohoku University. The initial model was calculated based on the fault parameters proposed by GFZ Potsdam and Tohoku University. Despite the limitations in the numerical simulation, generally the calculated tsunami heights and arrival times show a relatively good agreement with the observed ones. Based on the simulation it can be estimated that the tsunami wave may reach the west and north coast of northern Sumatra at about 15 to 25 and 20 to 30 minutes after the earthquake, respectively. The maximum calculated tsunami heights in the west and north coast of Aceh were about 11 to 24 and 8 to 15 m, respectively. The calculated arrival times show that the tsunami wave may reach west coast of Thailand and east coast of India and Sri Lanka at about 90 to 100 and 100 to 120 minutes after the earthquake, respectively. The maximum calculated tsunami heights at Phuket of Thailand and Tricomalee of Sri Lanka were about 4 to 5 and 1.5 to 3.5 m, respectively.